Quarter Life Crisis Sebagai Moderator Antara Resiliensi dan Kecemasan Masa Depan pada Dewasa Awal - Trinanti, Yuana Ika; Rohmadani, Zahro Varisna (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study focuses on the future anxiety of early adult individuals. With the aim of the relationship between resilience and future anxiety with quarter life crisis as a moderating variable. The population of this study were early adult individuals aged 20-29 years domiciled in Cilacap totaling 75 respondents. Based on the sampling method with purposive sampling. Hypothesis testing is done using Moderate Regression Analysis (MRA). The results of this study indicate that quarter life crisis has a positive effect on future anxiety. Resilience has no effect on future anxiety. Then, quarter life crisis has no effect on the relationship between resilience and future anxiety. Thus, quarter life crisis is unable to moderate the relationship between resilience and future anxiety.